[Horizon Scanning Of Therapeutic Alternatives For Generalized Myasthenia Gravis And Five-Year Healthcare Expenditure Forecast Model] - Adami, Silvia; Alboni, Paolo Emilio; Cristinziano, Adriano; La Seta, Concetta; Marinozzi, Andrea; Colalillo, Emanuele; Bitonti, Rossella (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
OBJECTIVE: The objective of the analysis was to assess and quantify the economic impact of generalized Myasthenia Gravis (gMG) in Italy over the next five years (2025—2029) using Horizon Scanning and expenditure forecasting methodologies.METHODS: The analysis is characterized by conducting Horizon Scanning of therapies for gMG that will be reimbursed in the Italian market over the next five years (2025—2029), followed by the development of a disease expenditure model for the same time frame. The Horizon Scanning methodology for gMG included research on ClinicalTrials.gov to identify relevant Phase 2 or 3 studies. A forecasting model was developed to evaluate the impact of new therapies for gMG from the perspective of the Italian National Health Service, considering total patient management costs. The analysis included acquisition and administration costs of treatments, as well as costs for managing exacerbations and myasthenic crises. The assumptions were validated by an expert panel.RESULTS: Horizon Scanning identified 14 new drugs for gMG in clinical development, with 7 of these expected to enter the Italian market between 2025 and 2029. The expenditure forecast analysis results indicate a slight increase in gMG treatment costs, stable administration costs and a slight reduction in costs for managing exacerbations and myasthenic crises. Total expenditure is projected to rise by 10.3%, from approximately €126 million in 2025 to €139 million in 2029.CONCLUSIONS: Through the Horizon Scanning and expenditure forecasting, it was estimated that, with the arrival of new therapeutic alternatives for gMG on the market, despite the high initial cost of these new treatments, their greater effectiveness could reduce the costs for managing exacerbations and myasthenic crises. This analysis provides essential information to improve the clinical management of the disease, optimize the allocation of healthcare resources and ultimately enhance the quality of life of patients with gMG.